Ischemic brain infarcts and intracranial haemorrhages following Russell's viper (Daboia russelii) bite in Sri Lanka. (January 2017) - Namal Rathnayaka, R.M.M.K.; Kularatne, S.A.M.; Kumarasinghe, K.D.M.; Ranaweera, Janaka; Nishanthi Ranathunga, P.E.A.
Abstract: Snakebite is an important medical problem in Sri Lanka. Of the deadly venomous snakes, Russell's viper ( Daboia russelii ) is widely distributed and responsible for most of the fatalities of snakebite in the country. It is not uncommon to see atypical manifestations in Russell's viper bite. We report the events of intracranial haemorrhages and multiple ischemic brain infarcts following Russell's viper ( Daboia russelii ) bite of a previously healthy 43-years-old male who succumbed to envenoming. Highlights: A fatal case of Russell's viper ( Daboia russelii ) bite is described. Patient's history, examination, investigations, management and autopsy findings are noted. Concurrence of intracranial haemorrhage and ischemic brain infarcts is the key feature. Clinical case that highlights the complex nature of Daboia russelii venom.